TAFSIR TARBAWI MANAJEMEN PENDIDIKAN DALAM AL-QURAN - Ibnurawandhy N. Hula; Yunita ibrahim; Rafli datundugon; Mariaty Podungge (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
In an Islamic perspective, managerial terms are very popular. However, when approaching the Arabic term here we can mean the individual organization "yudabbiru", directing, managing, executing, governing. Islamic education management is a unique process that focuses on how Islamic education can achieve efficient and effective teaching. The use of the name Al-Tadbir in the Qur'an to describe management. Some of the management principles mentioned in the Qur'an are as follows: faith, sincerity, kindness, exemplary, unity of direction, deliberation, accountability, efficient and effective, open, participative, responsible, competent, and cooperation. and a flexible approach to Al-Qur'an education each described as planning, organizing, actuating, controlling, and referred to as a management system.